Eighth grade students become proficient at CPR and use of an AED following a condensed training programme - Kelley, James; Richman, Peter B.; Ewy, Gordon A.; Clark, Lani; Bulloch, Blake; Bobrow, Bentley J. (Resuscitation, 2006)
To evaluate a new, 1-h, condensed training programme to teach continuous chest compression cardiopulmonary resuscitation (CCC-CPR) and automated external defibrillator (AED) skills to a cohort of eight grade public school students. Study design-prospective, interventional trial; Study population-convenience sample of students from two eighth grade classes; Study setting-urban, public school; Study protocol-written parental consent was obtained. Student attitudes, prior experience and baseline knowledge were sampled using an initial questionnaire and a modified American Heart Association (AHA) CPR/AED pretest. Students received training in continuous chest compression CPR (CCC-CPR) and AED use through a new condensed training programme. Student CCC-CPR and AED skills were immediately tested in a standardized fashion by the study team. Four weeks later, written and practical examinations were retaken by the same students supervised by the study team. Examination score differences were analyzed using matched pair t-tests. All tests were two tailed with alpha set at 0.05. Confidence Intervals (CI) 95% were calculated as appropriate. The primary outcome measure was the percentage of students who could correctly perform CCC-CPR and application/operation of an AED in a mock adult cardiac arrest scenario. Thirty-three eligible subjects completed the programme; mean age 13.7 years; 48.5% female. Eight participants reported some prior training in CPR and AED use. Following initial training, 29/33 (87.8%) subjects demonstrated proficiency at CCC-CPR and AED application/operation in a mock adult cardiac arrest scenario. At four-weeks, 28/33 (84.8%) subjects demonstrated skill retention in similar scenario testing. Subjects also showed improvement in written knowledge regarding AED use as shown by scores on an AHA based written exam (60.9% versus 77.3%; p < 0.001). With our focused, condensed training program, eighth grade public school students became proficient in CCC-CPR and AED use. This is the first study to document the ability of middle school students to learn and retain CCC-CPR and AED skills for adult sudden cardiac arrest victims with such a curriculum.